Corporate Governance’s Influence on Private Commercial Banks’ Financial Performance in Bangladesh - Neogy, Taposh Kumar; Rahman, Md. Obaidur (Asian Business Review, 2023)
Corporate governance is imperious to the banking sector’s growth. The study aims to explore how corporate governance mechanisms impact certain aspects of financial performance. This study has taken five listed conventional PCBs with a five-year study period from 2016 to 2020 using the purposive sampling technique. The influence of various CG mechanisms on financial performance attributes has been investigated through the use of multiple regression analysis. The study findings demonstrate that equity ratio, log total assets, and log listing age out of eight variables have a significant influence on NPM and ROA, while the other five variables revealed insignificant influence. On the other hand, ROE was influenced by log total assets and log listing age, but insignificant influence was found in the remaining six variables. Moreover, log listing age revealed a significant impact on EPS, whereas an insignificant influence has been observed in the case of the remaining seven variables. The study recommended that corporate governance must be adequate and transparent for the sake of pertinent stakeholders in the banking sector.